Chondroid syringoma of the upper lip: a rare entity - Goel, Ashiya; ., Aman; Raheja, Vinny; Kumari, Manisha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Chondroid syringomas are uncommon cutaneous neoplasms of sweat gland origin which are slow-growing, nontender, subcutaneous or intracutaneous in location and often occurring in the head and neck region. Chondroid syringoma should be considered in the differential diagnosis of any subcutaneous nodule over the face. The clinician may miss the diagnosis of this lesion and if it is suspected, tumour should be excised with a margin of normal tissue and regular follow up should be done.